Avoiding Overfitting: A Survey on Regularization Methods for Convolutional Neural Networks - Santos, Claudio Filipi Gonçalves Dos (2022)
Several image processing tasks, such as image classification and object detection, have been significantly improved using Convolutional Neural Networks (CNN). Like ResNet and EfficientNet, many architectures have achieved outstanding results in at least one dataset by the time of their creation. A critical factor in training concerns the network's regularization, which prevents the structure from overfitting. This work analyzes several regularization methods developed in the past few years, showing significant improvements for different CNN models. The works are classified into three main areas: The first one is called data augmentation,where all the techniques focus on performing changes in the input data. The second, named internal changes,aims to describe procedures to modify the feature maps generated by the neural network or the kernels. The last one, called label,concerns transforming the labels of a given input. This work presents two main differences comparing to other available surveys about regularization: (i) the first concerns the papers gathered in the manuscript, which are not older than five years, and (ii) the second distinction is about reproducibility, i.e., all works referred here have their code available in public repositories or they have been directly implemented in some framework, such as TensorFlow or Torch.